Using Assessments for Instructional Improvement: A Literature Review - Young, Viki M.; Kim, Debbie H. (Education Policy Analysis Archives, 2010)
The current educational reform policy discourse takes for granted the central role of using data to improve instruction. Yet whether and how data inform instruction depends on teachers’ assessment practices, the data that are relevant and useful to them, the data they typically have access to, and their content and pedagogical knowledge. Moreover, when one considers teachers’ organizational contexts, it is clear that school leadership and support for using data, capacity-building strategies, and the norms of adult learning and collaboration circumscribe opportunities to examine relevant data and to improve instructional practice in response. This literature review examines teacher as well as organizational practices and characteristics as they pertain to formative uses of assessment. We identify opportunities for important research to illuminate how and under what conditions teachers and schools as organizations can use data to inform instruction.